Exploring Water-Induced Helical Deformation Mechanism of 4D Printed Biomimetic Actuator for Narrow Lumen - Che Zhao; Lei Duan; Hongliang Hua; Jifeng Zhang (Machines)
To address the issues of limited adaptability and low spatial utilization in traditional rigid actuators, a biomimetic actuator with water-induced helical deformation functionality was designed. This actuator is capable of adaptive gripping and retrieval of objects in a narrow lumen. A numerical model was established to analyze its helical deformation mechanism, and the helical deformation characteristics of the actuator were calculated under different structural parameters. Based on four-dimensional (4D) printing technology, which integrates three-dimensional printed structures with responsive materials, experimental samples of biomimetic actuators were fabricated by combining thermoplastic polyurethane fiber scaffolds with water-absorbing polyurethane rubbers. By comparing the simulation results with the experimental data, the numerical model was corrected, providing theoretical guidance for the structural optimization design of the actuator. The experiment shows that the biomimetic actuator can act as a gripper to capture a small target in a lumen less than 5 mm in diameter. This research provides a theoretical and technical foundation for the development of specialized actuators aimed at narrow spaces.